QoS in GNU/Linux: its application on free Internet infrastructure - Charne, Javier (2012)
With the advent of VoIP transport and videoconferencing/telepresence equipment at relative low costs, companies started to use a single provider for data, telephony and video, thus causing three types of transport –with different characteristics and requirements- to converge in a single hard link. The current converging networks carry packages related to three different kinds of services (data, voice and video) and one of the usual classification criteria draws a distinction between traffic with strict time requirements and all other services. As bandwidth is always limited, it is necessary to identify and give priority treatment to this kind of traffic over others sharing the same medium. This paper discusses the assessment and application of different QoS tools on the free internet infrastructure for public spaces in the city of Junín, Buenos Aires, Argentina.